Interleukin-10 (IL-10) polymorphisms are associated with IL-10: Production and clinical malaria in young children - Zhang, Guicheng; Manaca, M.; McNamara-Smith, M.; Mayor, A.; Nhabomba, A.; Berthoud, T.; Khoo, S.; Wiertsema, S.; Aguilar, R.; Barbosa, A.; Quintó, L.; Candelaria, P.; et al. (2012)
The role of interleukin-10 (IL-10) in malaria remains poorly characterized. The aims of this study were to investigate (i) whether genetic variants of the IL-10 gene influence IL-10 production and (ii) whether IL-10 production as well as the genotypes and haplotypes of the IL-10 gene in young children and their mothers are associated with the incidence of clinical malaria in young children. We genotyped three IL-10 single nucleotide polymorphisms in 240 children and their mothers from a longitudinal prospective cohort and assessed the IL-10 production by maternal peripheral blood mononuclear cells (PBMCs) and cord blood mononuclear cells (CBMCs). Clinical episodes of Plasmodium falciparum malaria in the children were documented until the second year of life. The polymorphism IL-10 A-1082G (GCC haplotype of three SNPs in IL-10) in children was associated with IL-10 production levels by CBMC cultured with P. falciparum-infected erythrocytes (P=0.043), with the G allele linked to low IL-10 production capacity. The G allele in children was also significantly associated with a decreased risk for clinical malaria infection in their second year of life (P=0.016). Furthermore, IL-10 levels measured in maternal PBMCs cultured with infected erythrocytes were associated with increased risk of malaria infection in young children (P<0.001). In conclusion, IL-10 polymorphisms and IL-10 production capacity were associated with clinical malaria infections in young children. High IL-10 production capacity inherited from parents may diminish immunological protection against P. falciparum infection, thereby being a risk for increased malaria morbidity. © 2012, American Society for Microbiology.